Civil Legal Handling of Electronic Transactions: The Essence and Modern Realities - Zhumadilova, Mira A.; Dussipov, Yerkin Sh.; Arginbekova, Gulnar I.; Aitimov, Bolat Zh.; Milova, Yelena V. (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of the article is to consider the issue of civil law regulation of electronic transactions in many countries. [Methodology/Approach/Design] The authors used the dialectical method of cognition of social and legal phenomena and general scientific research methods, such as analysis, synthesis, a systematic approach. [Findings] General features of legal regulation of electronic transactions were explained. The relevance of electronic transactions is shown on the example of regulatory legal acts in this field in Kazakhstan. Advantages and disadvantages of digitalization in the field of electronic transactions were analysed. Special attention was paid to current realities of electronic transactions and electronic tendering during a pandemic. It was concluded that the advent of digital opportunities simplifies a life greatly, but since these relations are not directly regulated by the laws of several countries, great risks are created. And the adoption of new standards will reduce risks in terms of the circulation of digital rights, the purchase of financial assets and the use of new means of payment.